Choosing Club Membership under Tax Competition and Free Riding - Hyun Park; Apostolis Philippopoulos (Center for Economic Studies and ifo Institute (CESifo), 2003)
We study the choice of club membership, when member-countries' national governments set their tax policies non-cooperatively. Federal policy (in the form of club membership) has a higher constitutional status than national policies (in the form of income tax rates). This allows federal policy to reduce the inefficiencies arising from uncoordinated national policies. We show that equilibrium membership decreases with any factors that generate Nash-type inefficiencies; growing capital mobility is one such factor. In the particular case in which these inefficiencies take the form of tax competition for mobile tax bases and free riding on other countries' contribution to international public goods, one can rationalize the formation of very small economic unions only. The normative result is that union enlargement requires a switch from uncoordinated to coordinated national fiscal policies.
Keywords: 330; clubs; capital mobility; federalism